Psychological factors associated with substance use initiation during the COVID-19 pandemic - Rogers, Andrew H.; Shepherd, Justin M.; Garey, Lorra; Zvolensky, Michael J. (Psychiatry research, 2020)
•COVID-19 psychological factors may be risk factors for substance use initiation.•COVID-19-related worry is specifically related to using substances to cope during the pandemic.•COVID-19-related psychological factors may require specific clinical attention. The 2019 outbreak of the novel coronavirus (COVID-19) has had a devastating impact. Given the on-going nature of the outbreak, the deleterious toll on mental health, including substance use, is unknown. Negative reinforcement models of substance use posit that elevations in stress from the COVID-19 pandemic will elicit a corresponding motivation to downregulate COVID-19-related stress reactivity via substance use for a subset of the population. The current study sought to evaluate: (1) if COVID-19-related worry and fear were associated with substance use coping motives; and (2) how levels of COVID-19-related worry and fear differ between pre-COVID-19 substance users, COVID-19 substance initiators, and abstainers. Participants were 160 adults recruited nationally between April-May 2020 for an online study. Results indicated that COVID-19-related worry was associated with substance use coping motives. Additionally, compared to abstainers, pre-COVID-19 substance users and COVID-19 substance initiators demonstrated the highest levels of worry and fear. Examination of differences suggested that the COVID-19 substance initiators had the highest COVID-19-related worry and fear for all substances except for opioids, with effect size estimates ranging from small to medium. The results of this study suggest that COVID-19-specific psychological factors appear to be involved in substance use behavior.